PENYELESAIAN KONFLIK SOSIAL MELALUI PENGUATAN KEARIFAN LOKAL - Astri, Herlina (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
The difficulty to get a job, no equality before the law and other violations toward citizen’s rights, are widening social gap among people. Those trigger conflict among people and within community. This study aims at presenting a clearer picture on how local wisdom play its part on social conflicts resolution. It uses literature study and concepts interpretation related to some understanding on social conflict and local wisdom.